The role of ICT in smart specialization of EU regions - Dziembała, Małgorzata; Talar, Sylwia (Journal of Business Economics and Management, 2021)
The aim of the paper is to answer the overriding question what is the role of ICT in implementation of smart specialization (SS) in EU regions (NUTS2 level)? This role can be dual and ICT is considered in this study both as an invention which has led to the emergence of new sector, and from the perspective of general purpose technology (GPT) properties where ICT plays the role of input in innovation process. There are used following methods and techniques: desk research, descriptive statistical analysis, the correlation measure and Hellwig’s method of taxonomic analysis. The main findings indicate that in practice SS in ICT is not focused on development ICT as invention and is not based on readiness to usage of ICT as GPT. However, the abilities of regions to take advantage of ICT as a driver of innovation (as GPT) are materially related to specialization in the ICT sector (development ICT as invention). The findings bring some improvements by evidence-based policy making. The research contribute to the better understanding of the innovation determinants during digital transformation and especially the base of specialization in ICT as GPT under SS assumptions.